Granularity Decision of Microservice Splitting in View of Maintainability and Its Innovation Effect in Government Data Sharing - Yan Li; Chun-Zi Wang; Ying-chao Li; Jia Su (Discrete Dynamics in Nature and Society)
The reasonable sharing and effective integration of data is the premise of improving the comprehensive governance ability of society through data empowerment. It can be determined that the fine-grained splitting of microservice framework can promote the reasonable sharing and effective integration of data. However, how to determine the granularity of microservice splitting is a multiparameter and multiobjective decision-making problem, which is also a key basic problem to be solved urgently both in academic research and application. From the perspective of application, this paper puts forward the criteria and basic framework that can guide the microservice splitting, and for the first time, based on the perspective of maintainability, it gives the decision criteria and methods of microservice splitting granularity. After the theoretical research, this paper also takes the provincial microservice governance of food and drug regulation as an example: the example shows that the framework and methods proposed can effectively improve data sharing and system expandability. Through microservice governance, collaborative social governance featuring “one network to achieve management objectives, one network to realize comprehensive business processing, one network for comprehensive view of all information” can be achieved. It is an exemplary mode worth popularization.